Deficiency of Nox2 prevents angiotensin II-induced inward remodeling in cerebral arterioles - Chan, Siu-Lung; Baumbach, Gary L. (Frontiers in Physiology, 2013)
Angiotensin II is an important determinant of inward remodeling in cerebral arterioles. Many of the vascular effects of angiotensin II are mediated by reactive oxygen species generated from homologues of NADPH oxidase with Nox2 predominating in small arteries and arterioles. Therefore, we tested the hypothesis that superoxide generated by Nox2 plays a role in angiotensin II-induced cerebral arteriolar remodeling. We examined Nox2-deficient and wild-type mice in which a pressor or a non-pressor dose of angiotensin II (1000 or 200 ng/kg/day) or saline was infused for 4 weeks via osmotic minipumps. Systolic arterial pressure was measured by a tail-cuff method. Pressure and diameter of cerebral arterioles were measured through an open cranial window in anesthetized mice. Cross-sectional area (by histology) and superoxide level (by hydroethidine staining) of cerebral arterioles were determined ex vivo. The pressor, but not the non-pressor, dose of angiotensin II significantly increased systolic arterial pressure in both wild-type and Nox2-deficient mice. Both doses of angiotensin II increased superoxide levels and significantly reduced external diameter in maximally dilated cerebral arterioles in wild-type mice. Increased superoxide and inward remodeling were prevented in Nox2-deficient mice. Moreover, only the pressor dose of AngII increased cross-sectional area of arteriolar wall in wild-type mice and was prevented in Nox2-deficient mice. In conclusion, superoxide derived from Nox2-containing NADPH oxidase plays an important role in angiotensin II-mediated inward remodeling in cerebral arterioles. This effect appears to be independent of pressure and different from that of hypertrophy.